ADVANCED FOREIGN EXPERIENCES IN PRESCHOOL EDUCATION - Usmanova Saodat Erkinovna (Journals Park Publishing, 2022)
This in the article before school education in the field innovative technologies according to advanced foreign experiences about to information have to be can.
Keywords: before school education, advanced foreign experiences, innovative technologies, fashion and technology base, moral